An investigation of preservice teachers’ perceptions on the impact of formative assessment on enhancing students’ academic self-efficacy - Phạm Quỳnh Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is a study investigating pre-service teachers' perceptions of the impact of formative assessment on increasing students' academic self-efficacy. The study was conducted with primary preservice teachers to explore their perceptions on the use of formative assessment strategies and the impact on students’ academic self-efficacy via questionnaire and interviews. The findings show that pre-service teachers see formative assessment as an important tool for offering constructive feedback and acknowledging student progress, both of which are necessary for creating a pleasant learning environment and increasing self-efficacy. However, some obstacles have been discovered, including a lack of experience in this subject and a lack of understanding to provide appropriate feedback. The study concludes by recommending that teacher education programs incorporate significant formative assessment training and pointing out some limitations of this study. This study contributes to the larger educational discourse about how formative assessments might be designed to meet students' developmental needs and boost their self-efficacy in academic settings.